A carpal tunnel grading system including combined sensory index‐diagnosed mild cases: Relation to presenting features and outcomes. Issue 1 (3rd May 2017) - Zeidman, Lawrence A.; Pandey, Dilip K.
ABSTRACT: Introduction : Prior studies have demonstrated superiority of the combined sensory index (CSI) algorithm in diagnosing mild carpal tunnel syndrome (CTS) and have compared presenting symptoms to CTS grade. However, CTS symptoms, signs, and outcomes, including CSI‐diagnosed cases, have not been compared with CTS grade. Methods : We retrospectively studied 294 CTS hands from 2010 to 2013; stratified them into mild, moderate, and severe grades; and analyzed the association between CTS grade and presenting symptoms/signs and outcomes. Results : Sensorimotor symptoms ( P = 0.017) and signs ( P < 0.001) were significantly associated with CTS grade. Regardless of CTS grade, 94% of hands improved with surgery compared with 42% with conservative treatment ( P < 0.001). Even in mild CTS, 100% improved with surgery vs. 33% with conservative management ( P = 0.011). Discussion : These results corroborate prior studies that compared symptoms to CTS grade and suggest that more objective signs associate even better. CTS grades associate with outcomes, but additional studies are required. Muscle Nerve 57 : 45–48, 2018